2022
DOI: 10.1021/acs.biochem.2c00583
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Elevated Gene-1 Cys75 S-Palmitoylation by ZDHHC6 Regulates Its Biological Activity

Abstract: Nonalcoholic fatty liver disease is a major risk factor for hepatocellular carcinoma (HCC). Astrocyte elevated gene-1/Metadherin (AEG-1/MTDH) augments lipid accumulation (steatosis), inflammation, and tumorigenesis, thereby promoting the whole spectrum of this disease process. Targeting AEG-1 is a potential interventional strategy for nonalcoholic steatohepatitis (NASH) and HCC. Thus, proper understanding of the regulation of this molecule is essential. We found that AEG-1 is palmitoylated at residue cysteine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Among the few experimentally established substrates of zDHHC6, many are either type I or type II transmembrane proteins: CANX ( 25 , 27 ), TfR ( 25 , 26 ), the interferon-induced transmembrane protein 3 (IFITM3) ( 38 ), the tight junction protein angulin-1 ( 39 ), or the recently identified substrates AEG1 and CLIMP-63/CKAP4 ( 40 , 41 ). All these proteins display one or several cysteines in very close proximity to their TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Among the few experimentally established substrates of zDHHC6, many are either type I or type II transmembrane proteins: CANX ( 25 , 27 ), TfR ( 25 , 26 ), the interferon-induced transmembrane protein 3 (IFITM3) ( 38 ), the tight junction protein angulin-1 ( 39 ), or the recently identified substrates AEG1 and CLIMP-63/CKAP4 ( 40 , 41 ). All these proteins display one or several cysteines in very close proximity to their TMD.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of AEG-1-C75S mouse by CRISPR/Cas9 technology has been described ( 16 ). AEG-1-C75S heterozygote x heterozygote mating was performed to generate AEG-1-WT and AEG-1-C75S littermates.…”
Section: Methodsmentioning
confidence: 99%
“…AEG-1 functions as a scaffold in multiple steps in the activation process of NF-κB, a master regulator of inflammatory cytokines, and by activating NF-κB AEG-1 promotes inflammation ( 13 , 14 , 15 ). AEG-1 is a 582 amino acid protein that has a single cysteine at position 75 (Cys75) and we recently demonstrated that AEG-1 is palmitoylated at Cys75 ( 16 ). Palmitoylation, a post-translational modification in which fatty acids are covalently attached to cysteine residues, is largely recognized as a positive regulator of protein function ( 17 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, palmitoylation negatively regulates AEG-1 function by reducing the stability of AEG-1 and by reducing its affinity with its interacting proteins. Further, a different research group identified ZDHHC6 as the main palmitoyl transferase for AEG-1 and found that CRISPR/Cas9 knock-in mice with a palmitoylation-defective form of AEG-1 had increased signaling pathways and regulators that contribute to cell proliferation, motility, angiogenesis, and lipid accumulation [ 147 ]. Together, palmitoylation plays a negative regulatory role on AEG-1 function.…”
Section: Palmitoylation In Cancermentioning
confidence: 99%